Reconstruction of Climate Changes Based δ18Ocarb on the Northeastern Tibetan Plateau: A 16.1-cal kyr BP Record From Hurleg Lake - Ma, Xueyun; Wei, Zhifu; Wang, Yongli; Wang, Gen; Zhang, Ting; He, Wei; Yu, Xiaoli; Ma, He; Zhang, Pengyuan; Li, Shangkun; Wei, Jingyi; Fan, Qiaohui (Frontiers in Earth Science, 2021)
Hydroclimate evolution history and changes in the Tibetan Plateau play significant roles in depicting paleoclimate and evaluating climatic conditions in the coming future. However, the interaction of the westerlies and the Asian monsoon complicates our understanding of the mechanism of climate variation over the Tibetan Plateau. In this study, we assessed the paleoclimate of Hurleg Lake, which was previously located in the convergence area of the East Asian monsoon and westerly wind. We first reconstructed the climatic conditions based on fined-grained authigenic carbonate δ18O (δ18Ocarb), plants derived proxies of C/N, and n-alkanes derived δ13C31. In the Hurleg Lake, the δ18Ocarb was controlled by δ18O changes of the lake water and evaporation. The climate evolution since ~16.1 cal kyr BP can be classified into three stages. The Lateglacial (16.1~11.0 cal kyr BP) was characterized by a warm-wet climate in the beginning, followed by a cold-dry climate since 12.0 cal kyr BP. Typical warm and cold phases occurred during 14.8~12.0 cal kyr BP and 12.0~11.1 cal kyr BP, which may correspond to the Bølling/Allerød (B/A) and Younger Dryas periods, respectively. The early to mid-Holocene was generally characterized by a warm-wet climate; however, notable cold-dry intervals occurred at ~8.3 cal kyr BP. The late Holocene (after 4.8 cal kyr BP) displayed a significantly cold-wet climate. Finally, we examined the possible mechanisms responsible for the climate variability in the study area. The results showed that the long-term warm trend in the Lateglacial and colder trend after early Holocene was controlled by insolation. The Asian summer monsoon and the westerlies played a significant role in determining moisture sources during the Lateglacial. The East Asian monsoon contributed greatly to the moisture variation from the early to mid-Holocene, whereas the westerly winds dominated during the late Holocene. Combined, our findings highlight the complex changes in hydroclimate conditions since the last glacial in the Tibetan Plateau, and provide crucial implications for comprehending the hydroclimate pattern in the transition zone of westerlies and Asian monsoon.